I WILL THANK 30 ANSWERS OF THE FOR THE CORRECT ANSWER AND I WILL MARK BRAINLIEST. IT'S VERY URGENT PLS ANSWER
Attachments:
![](https://hi-static.z-dn.net/files/d87/5f188b366a1ef7fd34266576c6ba59f5.jpg)
Answers
Answered by
2
in cubic polynomial factorisation is done by assuming the factor of given polynomial which makes it 0.
Attachments:
![](https://hi-static.z-dn.net/files/db3/aa0b884406dc937859ce1dd723466265.jpg)
Answered by
1
Answer:
(x+1)(2x+3)(2x-1)
Step-by-step explanation:
4x³+8x²+x-3
=4x³+4x²+4x²+x-3
=4x²(x+1) +4x²+4x-3x-3
=4x²(x+1) +4x(x+1)-3x(x+1)
=(x+1)(4x²+4x-3)
=(x+1)(4x²+6x-2x-3)
=(x+1) ( 2x(2x+3)-(2x+3) )
=(x+1)(2x+3)(2x-1)
Similar questions
English,
3 months ago
English,
3 months ago
Social Sciences,
7 months ago
Chemistry,
7 months ago
Physics,
1 year ago